Language Used by Chinese Malaysian Students Studying at an Australian University - LIAO, Chih-I (Issues in Language Studies, 2020)
In Australia, more than 33% of total international students are Mandarin speakers. Mandarin has become a common language in the international student community in Australia. Speaking Mandarin is important while studying in an English-speaking country. This article explores Chinese Malaysian students’ language proficiency and their language attitudes. Five participants were selected from an Australian university, they were interviewed based on sociolinguistic case study research. The language proficiency of five participants was classified at five levels and the participants were required to self-rate in all their languages in the questionnaire. The findings show that three of the five participants preferred speaking English in Australia while the other two felt more confident of speaking Mandarin. All participants claimed that living in Australia, English and Mandarin are equally important. In contrast, the five participants’ Bahasa Melayu proficiencies had largely decreased because of less practice and negative attitudes.